Changes in milk yield in relation to reproductive performance in suckled and non-suckled buffaloes - SINGH, A K; BRAR, P S (The Indian Journal of Animal Reproduction, 2023)
High milk yield, a common aim in co.nmercial dairy farming system in the developing countries, delays the onset ofovarian activity in dairy buffaloes. The present study was, therefore, conducted on six suckled and nine non-suckled buffaloesat organized dairy farms to determine alterations in milk yield during estrus and its effect on reproduction in buffaloes.Colustrum on the day of calving was I 0.23 ± 0.52 kg in suckled and 9.96 ± 0.32 kg in non-suckled buffaloes. Peak milk yield(kg) was significantly higher (P < 0.05) in suckled than in their non-suckled counterparts (13.75 ± 0.39 vs 12.53 ± 0.25).However, duration of peak yield was significantly (P < 0.05) longer in non-suckled buffaloes ( 41.22 ± 4.46 vs 31.5 ± 4.28days). Milk yield on the day of first post-partum estrus, two days pre- and post-estrus was 9.57 ± 0.63, 10.42 ± 0. 75 and10.54 ± 0. 72 kg in suckled and 9.21 ± 0.65, 10.68 ± 0.5 and I 0.84 ± 0.87 kg in non-suckled buffaloes. Milk yield was least inbuffaloes while they were in estrus. Buffaloes which did not conceive had significantly (P < 0.05) higher peak yield (I 4.5 ± 0.0kg/day in suckled and 14.2 ± 0.96 kg/day in non-suckled) as compared to their conceived counterparts (12.76 ± 0.9 kg/day insuckled and 12.3 ± 0.93 kg/day in non-suckled). These results suggest that high milk yield appears to suppress ovarian activityduring the early post partum period in dairy buffaloes.
Keywords: Buffaloes; conception; estrus; LH; milk yield; non-suckled; suckled